2018
DOI: 10.4103/ija.ija_354_18
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of post-dural puncture headache following spinal anaesthesia and accidental dural puncture from a non-obstetric hospital: A retrospective analysis

Abstract: Background and Aims:Post-dural puncture headache (PDPH) is one of the complications following spinal anaesthesia (SA) and accidental dural puncture (ADP). In our institute, we routinely practice epidural analgesia (EA) for supra-major surgeries. Our previous audit on EA revealed 4% incidence of ADP. This lead us to a clinical initiative to follow-up patients with dural puncture (DP) to note the incidence, presentation, associated symptoms and treatment of PDPH. Herewith, we present the retrospective analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Clinical research has shown that the use of smaller-gauge needles, particularly of the pencil-point design, are associated with a lower risk of PDPH than cutting-point needle tips. [ 3 4 ] However, the cost and lack of availability of the pencil-point needles make it difficult to be routinely used in parturients, especially in low-income countries. Neuraxial narcotics were found to reduce the incidence of PDPH after accidental dural puncture (ADP) during epidural anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research has shown that the use of smaller-gauge needles, particularly of the pencil-point design, are associated with a lower risk of PDPH than cutting-point needle tips. [ 3 4 ] However, the cost and lack of availability of the pencil-point needles make it difficult to be routinely used in parturients, especially in low-income countries. Neuraxial narcotics were found to reduce the incidence of PDPH after accidental dural puncture (ADP) during epidural anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…These findings spot light on a possible role for patients' age, BMI and vasomotor tone insatiability and development of PDPH and go in hand with Peralta et al [30] & Franz et al [31] who detected decreased PDPH incidence after Dural puncture in parturient with an increased BMI. Also, Bakshi & Gehdoo [32] and Özcan et al [33] detected a relation between incidence of PDPH and parturient age and found incidence was higher in age group of 20-40 years compared to older patients.…”
Section: Discussionmentioning
confidence: 98%
“…Time to ambulation has not been found to be a factor affecting the incidence of PDPH. [ 25 ] A meta-analysis of the effectiveness of bed rest after dural puncture on PDPH concluded that PDPH prevalence did not differ between the groups assigned to 24 hours of bed rest or early ambulation. [ 26 ] A Cochrane review found that bed rest increased PDPH compared to early ambulation.…”
Section: Discussionmentioning
confidence: 99%